Subacute liver failure due to autochthonous hepatitis E virus infection in an elderly man in the United States - Marie L. Landry; Saleem Kamili; Dhanpat Jain (Elsevier, 2018)
Hepatitis E virus (HEV) infection in immunocompetent individuals is uncommon in the United States. We report a case of elderly man who presented with jaundice, cholestatic hepatitis, and subacute liver failure with fatal outcome. The patient was started on steroids based on ANA positivity. Liver biopsy showed panlobular hepatitis with cholestasis. The histologic differential diagnosis included drug/toxic injury, biliary obstruction, and acute hepatitis C or hepatitis E. Drug/toxic injury was favored initially. However, subsequent serology was positive for anti-HEV IgM and IgG, and HEV RNA genotype 3 was detected in both serum and liver tissue. Awareness of autochthonous hepatitis E and its inclusion in the differential diagnosis is needed for early diagnosis and appropriate management.